Preparation of bio-polyol via bamboo wastes liquefaction and the effects of bleaching by Hydrogen Peroxide treatment - Mohammad Suffian James, Redzuan; Md Tahir, Paridah; Mohd Yusof, Norwahyuni; Al-Edrus, Syeed SaifulAzry Osman; Zainal Abidin, Zurina; Mohamed Yusoff, Mohd Zuhri; Lee, Seng Hua; San, H’ng Paik (Springer, 2025)
In this study, polyols have been prepared via liquefaction of wastes of four types of bamboo, namely, Dendrocalamus asper (Betong), Gigantochloa levis (Beting), Bambusa vulgaris (Minyak), and G. scortechinii (Semantan). The effects of reaction temperatures and times on the yield percentage, hydroxyl number and viscosity were investigated. The study revealed that under a temperature of 150 °C and a duration of 60 min, the most optimum results were achieved, including a yield of 94.59%, a hydroxyl number of 342.83 mg KOH/g, and a viscosity of 231.60 cP. The study also suggests that a mixture of bamboo wastes can be used for the liquefication process to obtain a comparable result with bamboo waste of single species, which is more practical for the industries to adopt. The polyols produced were dark brown in colour and they were undergone bleaching process using hydrogen peroxide with potassium carbonate serving as the activator. The colour of the liquefied bamboo polyol was successfully changed to a light yellowish tone by adding 60% hydrogen peroxide and stirring for a period of 12 h. Fourier Transform Infrared (FTIR) results showed that bleached and unbleached bamboo polyols only showed slight distinctions indicates that the chemical composition and structure of the untreated liquefied bamboo did not undergo significant changes as a result of the bleaching process.